IMPLEMENTASI KEBIJAKAN DANA DESA TAHUN 2018 DI KECAMATAN LIRUNG KABUPATEN KEPULAUAN TALAUD - PIOH, NOVIE; WAWORUNDENG, WELLY; LUMI, HENDRA (JURNAL ADMINISTRASI PUBLIK, 2020)
The policy of the village fund is beneficial to the community, because the village is the frontlineand is in contact as well as interact directly with the residents of the village. This became the basis of thecurrent government in order to build Indonesia starts from the village, and supported by theadministration of village funds in order to improve the welfare of the community, create jobs, and reducepoverty in this study the problem of human resources, the attitude of the committe, aspects of the policyinterests of the government district dominates the program implementation of village.In this study, using qualitative research methods to know about the implementation of the policyof the village fund in the district Lirung. From the results of the study showed that the interests of thepolicy of the district government that affect the implementation of the policy of the village fund, so that theaspirations of the community are not fully accommodated.Keywords : Implementation, Policy, the Village Fund.